2022
DOI: 10.1111/eth.13352
|View full text |Cite
|
Sign up to set email alerts
|

Tool use and tooling in ravens (Corvus corax): A review and novel observations

Abstract: Corvids are known for their cognitive flexibility, and many have innovated various forms of tool use. Here, we review tool use and tooling in common ravens (Corvus corax) and describe additional observations. In total, they have used tools in 10 submodes and 11 modes. Of these modes, four were observed in captivity only, four in the wild only and three in both contexts. Five of these modes constitute tooling. When they manufactured tools, it was through detachment or subtraction. The purpose of most tool use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…Presumptive tool use in Northern ravens was reported as early as 1987 [62] and has been described in laboratory-based experiments more recently, in which ravens displayed future planning and tool use at a level of proficiency seen in apes, suggesting an evolutionary cognitive pathway for these behaviours [63]. A recent review of tool use and tooling in ravens by Jacobs and Osvath [64] identified 11 modes of tool use with specific tool use (such as twigs, stones and pinecones) in 10 sub-modes. Other sub-modes identified the use of water to soak foodstuff, the exchange of tokens with conspecifics and placing food within an object, such as a piece of cloth, and folding it over.…”
Section: Can Perforation Strategiesmentioning
confidence: 96%
“…Presumptive tool use in Northern ravens was reported as early as 1987 [62] and has been described in laboratory-based experiments more recently, in which ravens displayed future planning and tool use at a level of proficiency seen in apes, suggesting an evolutionary cognitive pathway for these behaviours [63]. A recent review of tool use and tooling in ravens by Jacobs and Osvath [64] identified 11 modes of tool use with specific tool use (such as twigs, stones and pinecones) in 10 sub-modes. Other sub-modes identified the use of water to soak foodstuff, the exchange of tokens with conspecifics and placing food within an object, such as a piece of cloth, and folding it over.…”
Section: Can Perforation Strategiesmentioning
confidence: 96%
“…Ravens are capable of planning for tool use (throwing a rock into a transparent tube to get bait off a rocking platform) and bartering with delays of up to 17 h (Kabadayi and Osvath 2017 ). Although ravens' tool use in the wild may be more common than widely perceived (Jacobs and Osvath 2023 ). Thus, non-tool-using species can often display comparable cognitive abilities to tool-users on tool-related tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps particularly interesting is the observation of such capacities in birds, whose brain anatomy is distinctly different from that of mammals [1,2]. At least some birds are innovative tool manufacturers [3] and users [4] who can plan for the future [5][6][7] and engage in causal reasoning [8]. Others show remarkable long-term memory capacity [9][10][11][12], inference [10], episodic-like memory [11], and striking regularity in how they use past experience to navigate novel present conditions [13].…”
Section: Introductionmentioning
confidence: 99%